Exports, and Foreign Distributional Activities: Evidence on Japanese Firms in the United States - Yamawaki, Hideki (The Review of Economics and Statistics, 1991)
The relationship between Japanese exports to the United States and distributional activities of Japanese affiliates in the U.S. wholesale trade sector is examined by using a sample of forty-four three-digit Japanese exporting industries matched to U.S. industries. The statistical analysis provides evidence supporting the hypothesis that Japanese direct investment in distribution has strongly promoted Japanese exports to the U.S. markets. Copyright 1991 by MIT Press.